The Effect of Marketing Mix on Super Air Jet Customer Loyalty at Soekarno-Hatta International Airport - Anita Meistika; You She Melly Anne Dharasta (CV. Rayyan Dwi Bharata, 2023)
Transportation has an important and strategic role in implementing the archipelago concept and in strengthening relations between nations. Methods and tools for creating customer satisfaction using this marketing mix refers to customer retention as an obligation to buy or reuse a product or service. with Super Air Jet airlines. The survey method is a quantitative method by collecting a sample of 100 respondents by distributing surveys via Google Forms using data collection technology. The purpose of this study is to identify and analyze the marketing mix of its Superair jets at international airports and its effect on customer loyalty. Soekarno Hatta. The results of this study concluded that the marketing mix variable has value. From this it can be concluded that H1 is accepted or rejected as the marketing mix variable (Y) which affects customer loyalty. Several respondents agreed and specifically agreed with the survey results. Superjet physical signs such as: B. Automatic check-in facilitates passenger check-in. The market mix produces a positive coefficient of determination with an R-squared value of 0.771. From these results, there is an influence of marketing mix variables on customer loyalty of super air jet airlines of 58.9%.